Reduced 123I Ioflupane Binding in Bilateral Diabetic Chorea: Findings With 18F FDG PET, 99mTc ECD SPECT, and 123I MIBG Scintigraphy. (June 2016) - Sato, Kenichiro; Hida, Ayumi; Kameyama, Masashi; Morooka, Miyako; Takeuchi, Sousuke
Abstract : Abstract: We report a 64-year-old man with diabetic chorea whom we investigated with dopamine transporter SPECT, 18 F FDG PET, 99m Tc ethylcysteinate dimer (ECD) SPECT, and 123 I metaiodobenzylguanidine (MIBG) scintigraphy. Dopamine transporter SPECT revealed reduced 123 I ioflupane binding in the bilateral striatum. 18 F FDG PET showed metabolic dysfunction in the bilateral striatum, as shown in earlier studies. 99m Tc ECD SPECT revealed reduced brain perfusion in the bilateral caudate nucleus and putamen. 123 I MIBG scintigraphy revealed no cardiac sympathetic nerve dysfunction. Our case suggests a possible nigrostriatal presynaptic dopaminergic involvement in diabetic chorea.